Sociocultural dimensions of lexis and text in the history of English - International Conference on English Historical Linguistics 2014 : Louvain, Belgium); Petré, Peter (Linguist); Cuyckens, H.; D'Hoedt, Frauke (Amsterdam ; Philadelphia : John Benjamins Publishing Company, 2018)
The chapters collected in this volume examine how the sociohistorical and cultural context may influence structural features of lexis and text types. Each paper pays particular attention to social 'labels' and attitudes (conservative, religious, ideological, endearing, or other), thereby focusing on their dynamic and historical dimension. Changes in these are analyzed in order to explain morphological, lexical, and textual changes that would otherwise be hard to account for. Together, they provide a varied window on the effect of historical versions of a dynamic society on lexis and text. Examining lexical and textual change in history from a sociocultural perspective teaches us a great deal - not just about the past, but it also makes us think about similar phenomena in the present, enhancing our knowledge about how universally human some of these phenomena are.
Introduction: philology as linguistically informed cultural history / Peter Petré and Hubert Cuyckens -- Conspicuous lexical choice in past societies. Old English ead in Anglo-Saxon given names: a comparative approach to Anglo-Saxon anthroponomy / Olga Khallieva Boiché -- News and relations: highlighted textual labels in the titles of early modern news pamphlets / Carla Suhr -- "All spirits, and are melted into air, into thin air": metaphorical connections in the history of English / Marc Alexander and Christian Kay -- Historical layers in text and genre. Conservatism and innovation in Anglo-Saxon scribal practice / Christine Wallis -- Old English wills: a genre study / Lilo Moessner -- Spatio-temporal systems in Chaucer / Minako Nakayasu -- "A riddle to myself I am": argument shifting in English congregational song between 1500 and 1900 / Kirsten Gather -- Lexis, morphology, and a changing society. Common to the North of England and to New England: British English regionalisms in John Russell Bartlett's Dictionary of Americanisms / Javier Ruano-Garrcía -- Betwixt, amongst, and amidst: the diachronic development of function words with final / st/ / Ryuichi Hotta -- English word clipping in a diachronic perspective / Donka Minkova.
Selected papers presented at the 18th International Conference on English Historical Linguistics, (ICEHL18), held at the University of Leuven, July 14-18, 2014.
Includes bibliographical references and index.
Online resource; title from digital title page (viewed on July 12, 2018).
eBooks on EBSCOhost
Keywords: English language -- History -- Congresses; English language -- Grammar, Historical -- Congresses; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; English language -- Grammar, Historical; English language; English language -- Social aspects; Historical linguistics; Sociolinguistics; Conference papers and proceedings; History